2019
DOI: 10.1186/s12885-019-5501-z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the transcriptional program of feline injection-site sarcoma using a cross-species mRNA-sequencing approach

Abstract: Background Feline injection-site sarcoma (FISS), an aggressive iatrogenic subcutaneous malignancy, is challenging to manage clinically and little is known about the molecular basis of its pathogenesis. Tumor transcriptome profiling has proved valuable for gaining insights into the molecular basis of cancers and for identifying new therapeutic targets. Here, we report the first study of the FISS transcriptome and the first cross-species comparison of the FISS transcriptome with those of anatomicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 89 publications
(105 reference statements)
0
15
0
Order By: Relevance
“…FFAR3 gene expression was found in the colon, cecum, thymus, spleen, pancreas, adipose tissue, lungs, duodenum, jejunum, and ileum of the New Zealand rabbit [90]. FFAR3 gene was reported to be absent in chicken genome [91]. FFAR3 was also found to express in adipose tissues of goats [111] and sheep [112].…”
Section: Ffar3 Expressionmentioning
confidence: 98%
See 1 more Smart Citation
“…FFAR3 gene expression was found in the colon, cecum, thymus, spleen, pancreas, adipose tissue, lungs, duodenum, jejunum, and ileum of the New Zealand rabbit [90]. FFAR3 gene was reported to be absent in chicken genome [91]. FFAR3 was also found to express in adipose tissues of goats [111] and sheep [112].…”
Section: Ffar3 Expressionmentioning
confidence: 98%
“…In New Zealand rabbits FFAR2 expresses in thymus, spleen, pancreas, adipose tissue, lungs, duodenum, jejunum, cecum ileum and colon [90]. In chickens, FFAR2 paralog genes are expressed in the testis, spleen, peripheral blood mononuclear cells (PBMC)s, adipose tissues, intestine, lung, liver, pancreas, ovary, thigh muscle, pectoralis muscle, eye, skin, subcutaneous adipose tissues, kidney, brain, heart, and uropygial gland [91]. Feline and canine soft tissue sarcoma as well as normal skin of felines and skeletal muscle of canines also showed the FFAR2 expression [92].…”
Section: Ffar2 Expressionmentioning
confidence: 99%
“…In the study, researchers articulate three upregulated genes in particular, including fibroblast activation protein alpha (FAP-alpha), a cell surface serine protease, Wilms tumor 1 (WT1), a tumor suppressor and transcription factor, and preferentially expressed antigen in melanoma (PRAME), as well as downregulated tumor suppressors TP63, EPHA1, and DUSP26. In the study, GSK-1059615, an inhibitor of PI3K and mTOR in humans, was found to lower FISS cell growth, indicating PI3K and mTOR pathways could potentially be considered in new therapies [12].…”
Section: Sarcomamentioning
confidence: 94%
“…Hyperthermia-induced gene immunotherapy with adenoviral feline IL-12 has been studied in spontaneous feline fibrosarcoma: intratumoral expression of the gene with limited systemic toxicity was achieved [85]. Enrichment of genes associated with IL-2 and IL-12 was also found in FISS cell lines [12].…”
Section: Sarcomamentioning
confidence: 99%
See 1 more Smart Citation